Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have a linear birth death process with birth rates $\lambda n$ and death rates $\mu n$ .

Let r(t) be the probability of extinction by time t. If there is 1 individual alive at time 0 explain why

r(t) = $\int^t_0 e^{-(\mu+\lambda)s}(\mu+\lambda r(t-s)^2)ds$

With r(0)=0 I have done this but the next bit is to derive a differential equation for r and solve it (at least in the case where $\mu\neq\lambda)$ and show that if $\mu>\lambda $ then r(t)--> 1 whereas if $\mu<\lambda $ then r(t) --> $\mu/\lambda$

I wanted to proceed as we do similar things in lectures.

So step 1 : multiply by $e^{(\lambda +\mu)t}$

This gives $e^{(\lambda +\mu)t}r(t)$ = $\int^t_0 e^{(\mu+\lambda)(t-s)}(\mu+\lambda r(t-s)^2)ds$

Then I let t-s = k to get $e^{(\lambda +\mu)t}r(t)$ = $\int^t_0 e^{(\mu+\lambda)(k)}(\mu+\lambda r(k)^2)dk$

I then differentiate both sides $e^{(\lambda +\mu)t}r'(t)+ (\lambda +\mu)r(t)e^{(\lambda +\mu)t}$ = $e^{(\mu+\lambda)(t)}(\mu+\lambda r(t)^2)$

Divide all terms by $ e^{(\mu+\lambda)(t)}$ Rearrange to get $dr/(r(t)(r(t)\lambda -\lambda -\mu)) = dt\mu$

Then separate into partial fractions

This gives $[-1/(\lambda+\mu r(t))] + [\lambda/((\lambda+\mu)(r(t)\lambda-\lambda-\mu))] = dt\mu$

Integrate both sides between t and 0

$[-1/(\lambda+\mu).lnr(t) + 1/(\lambda+\mu).ln(r(t)\lambda-\lambda-\mu)]^{r(t)}_{r(0)}= \mu t$

When I evaluate this at the limits and rearrange I get $[\lambda r(t)-\lambda-\mu]/r(t) = -(\mu + \lambda)e^{\mu t(\lambda + \mu)} = D$

Finally I rearrange to get $r(t) = (\lambda+\mu)/(\lambda - D)$ which does not have the qualities required, what have a done wrong?

share|cite|improve this question

The trouble is that you rearrange wrong... In fact, $$ r'(t)+(\lambda+\mu)r(t)=\mu+\lambda r(t)^2, $$ hence $$ \frac{r'(t)}{\lambda r(t)^2-(\lambda+\mu)r(t)+\mu}=1. $$ The decomposition into simple fractions reads $$ \frac1{\lambda r^2-(\lambda+\mu)r+\mu}=\frac1{\lambda -\mu}\left(\frac1{r-1}-\frac{\lambda}{\lambda r-\mu}\right). $$ Can you finish?

share|cite|improve this answer
thanks for your help, in the case of $\mu < \lambda$ is it right to use L'Hopitals rule? Thanks – Rosie Mar 6 '13 at 22:17
L'Hopital? What for? First thing would be to write down r(t) starting from my indications. – Did Mar 7 '13 at 3:09

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.